Problem-Solving Cycle Analysis in Finance Department of Hospital - Darmastuti, Meirina; Hartono, Budi (Universitas Teuku Umar, 2023)
One of the factors in the success of a hospital is the extent to which the finance department can effectively manage funds. Financial reports prepared by applicable regulations can evaluate the hospital’s financial performance and become a tool in strategic decision-making. This research is a qualitative descriptive study using action research, the method, and problem-solving cycle analysis, which consists of five steps: situation analysis and problem identification, prioritization of problems and goals, analysis of the causes of problems, determination of alternative problem-solving, and plans of action. Research data were taken from interviews, review of annual financial reports, and minimum financial service standard reports: cost recovery, speed of information about hospitalization bills, and timeliness of preparing financial reports. This study aims to identify and solve problems in the finance department of the Bogor Islamic Hospital so that it can improve the performance and competitiveness of the hospital in a timely and cost-effective manner. Through the analysis of the problem-solving cycle, it was found that the priority problem was the analysis of incomplete financial statements. Then found the causes and alternative solutions to problems from human factors, money, materials, machines, methods, markets, and the environment. A plan of action has been made to resolve the finance department's priority problem, including creating a guidebook of financial reports, counseling to increase motivation to learn, and training for finance department employees. These solutions are expected to be promptly implemented and beneficial for the growth and development of the Bogor Islamic Hospital, especially the hospital’s finance department.